Filament Damage in Bi2Sr2CaCu2O8-x (Bi-2212) Superconducting Wires Exposed by External Etching - Enger-Schnitzler, Jordan; Hopp, Christopher; Putney, Alexandra; Jewell, Matthew C. (My University, 2018)
We are studying Bi2Sr2Ca1Cu2Ox (Bi-2212): a superconducting material that is able to produce magnetic fields greater than 25 T. The study of sub-atomic particles in physics is progressing and needs higher magnetic fields for large particle accelerators. Bi-2212 is currently the only superconducting round wire capable of producing magnetic fields in excess of 20 T. Bi-2212 filaments in the silver matrix are brittle and vulnerable to damage during mechanical testing. This research seeks to understand how the damage varies under different stress and wire orientation testing conditions, and how that damage influences the wire’s electrical properties
Color poster with text, images, charts, photographs and graphs.
Keywords: Filaments; Bi-2212; Superconductors; Posters